Perierapan Yurisdiksi Alien Tort Claim Act Dalam Perspektif Hukum Pidana Internasional - sefriani sefriani (Fakultas Hukum Universitas Islam Indonesia, 2006)
ATCk restricts its jurisdiction by imposing some doctrines such as minimum contact, forum non-convenience, political question, international commuty and act of state doc trine. Besides that, it also ignores the international criminal law principles such as presumption of innocence, expeditious trial, equity ofarms and the atendance ofthe suspect in the court. The existence of par im parem in habet Imperium principle recognized ininternational law causes the decision of American Courtis meaningless.